ASSESSMENT OF GENETIC VARIABILITY AND ASSOCIATION BETWEEN YIELD AND YIELD COMPONENTS IN INDIGENOUSLY DEVELOPED CHILLI HYBRIDS (C apsicum annuum L.) - Z. Elahi; N. N. Nawab; T. N. Khan; A. Ramzan; M. U. Qasim; T. Noor; M. S. Tariq; M. Farooq (Journal of Animal and Plant Sciences, 2019)
There is a considerable scope for developing hybrids in chillies. Impact of indigenously developed chilli hybrids was assessed for the major yield determining traits viz; number of fruits, fruit weight, pericarp weight, seed weight, fruit length, fruit width and fresh fruit yield. Difference among the genotypes was observed to be significant for all the traits. The indigenous chilli hybrids HYB-5 (36.69 t/ha) and HYB-1 (36.17 t/ha) contributed maximum green fruit yield as compared to the commercial hybrid 222-HYB (28.42 t/ha) and the local varieties [Tatapuri (16 t/ha) and Lounghi (4.60 t/ha)]. The traits like number of fruits per plant, fruit length, fruit weight, pericarp weight and fresh fruit yield not only exhibited high PCV and GCV values but also high worth of heritability in broad sense (86% to 99%) and high genetic advance (32.85% to 60.66%) which signified the existence of large variability, with the least involvement of the environmental factors on the expression of these traits which may be utilized through selection for better improvement. Moreover, the correlations (genotypic) were generally higher than the correlations at phenotypic basis. Fruit length, number of fruits per plants, pericarp weight and fruit weight were positively and significantly correlated to fresh fruit yield. This, in other, words signposted the involvement of additive gene action in the manifestation of these characters and can perform well to selection after establishing a meaningful correlation with fresh fruit yield. However, a non-significant correlation existed between fresh fruit yield and seed weight.
Keywords: Fresh fruit yield; chillies; correlation; GCV; PCV; GA and h Fresh fruit yield; chillies; correlation; GCV; PCV; GA and h2